Management and Uses of Freshwater Swamp Forest at Bung Chi-Long in Phonngam Sub-district, Kosumphisai District, Maha Sarakham Province. - เหนือศรี ชมภู่; กุดแถลง นุกูล (Journal for Developing the Social and Community, 2016)
This research aims to 1) study the uses of Freshwater Swamp Forest at Bung ChiLong 2) study the communities participation in management of the Freshwater Swamp Forest, and 3) study the guidelines for managing Freshwater Swamp Forest at Bung Chi-Long by the sample consisted of 326 persons and the questionnaires and discussion as a means for collecting data. Findings were as follows: 1) The community uses the Swamp Forest at Bung Chi-Long, various aspects such as a source of food, medicinal plants, recreation sites, animal feeding sources, learning sources, including the folk ritual place. 2) The community people participation in management of Freshwater Swamp Forest at Bung Chi-Long of citizens at moderate level (  x = 3.00). 3) Seminar people gave these suggestions: taking some regulations for the uses of the forest, supporting budget from government for joint management of forest conservation and uses of local beliefs of cultural forest to manage the forest.